Type 2 Diabetes Mellitus Risk Level, Cardiovascular Diseases Risk Level, and Quality of Work Life among University Staffs; Correlational study - Titis Kurniawan; Eka Afrimasari; Sri Hartati (Jurnal Keperawatan Padjadjaran, 2018)
Type 2 diabetes mellitus and cardiovascular diseases are two of the most serious health problems produce wide negative impacts in Indonesia. Both diseases shares similar risks factors and may affect individual’s health status and quality of work (QoWL). Unfortunately, there is no evidence reported the chronic diseases risk level and their correlation with QoWL among university staffs in Indonesia. This correlational study aimed to identify the risk level of Type 2 diabetes mellitus (T2DM) and cardiovascular diseases and it correlation with the QoWL among university staffs. As many as 125 university staffs from one of public university in West Java – Indonesia were recruited randomly and asked to complete Finnish Diabetes Risk-Assessment form, The Jakarta Cardiovascular Scale, and quality of work life (QoWL) Evaluation Scale. The collected data were analyzed using descriptive and Pearson Correlation test. Results showed that nearly half of respondents had chronic diseases risk elevation; T2DM (40.39) and cardiovascular diseases (49%). Additionally, more than half of them (52.40%) perceived that their QoWL was less satisfied. It was found there was a significant relationship between T2DM risk level and cardiovascular diseases risk (r = 0.513; p=0.00); however, there was no significant correlation, neither between T2DM risk level (p=0.54) nore cardiovascular disease risk level (p = 0.19) with QoWL. To summarize, the university staffs are vulnerable for developing chronic diseases and have less satisfied QoWL. Therefore, it is important for the university to develop policy or program that enhances the employees’ opportunity in managing the risk and improving their health status and QoWL.